Kaginhawaan in the Context of Survival: Street Children’s Struggle for Well-Being - Irene Gonzales; Lanz Daenielle Cordero; Andrie Jann Akilith; Miguel Madamba Jr (Advanced Qualitative Research, 2025)
This study examines the well-being of street children, focusing on how they navigate daily struggles and find comfort despite challenging circumstances. With an estimated 150 million street children worldwide, including 250,000 in the Philippines, these children face unstable living conditions, abuse, and limited access to basic services. Drawing on Kaginhawaan, a Filipino wellness theory, and using Interpretative Phenomenological Analysis, this research explores how social, emotional, economic, occupational, and spiritual factors shape their resilience. Through participant narratives, five key themes emerged: (1) Atypical Family, revealing broken or nontraditional family ties; (2) Street Hustles, highlighting the survival work children engage in to meet basic needs; (3) Street Struggles, addressing bullying, exploitation, and lost childhoods; (4) Burden of Survival, focusing on exhaustion, debt, and social stigma; and (5) Faith in Survival, which illustrates how spirituality provides strength, comfort, and hope. These themes reflect how children construct meaning and preserve dignity amid harsh realities. The findings affirm that even in survival mode, children draw from internal and external resources, particularly faith, social bonds, and emotional resilience, to endure. Rooted in Kaginhawaan, the study emphasizes the importance of nurturing environments, compassion, and holistic interventions that support both immediate needs and long-term well-being. It highlights the complexity of street children's lives and how they find comfort not in the absence of struggle, but in their response to it. Ultimately, the research calls for policies and programs grounded in empathy and cultural insight to address the multifaceted needs of this vulnerable population.